2011
DOI: 10.1093/heapol/czr043
|View full text |Cite
|
Sign up to set email alerts
|

Trends in hospitalizations for primary care sensitive conditions following the implementation of Family Health Teams in Belo Horizonte, Brazil

Abstract: Though the ecologic nature of our study limits the confidence with which conclusions can be affirmed, the Family Health Strategy appears to have contributed to a major reduction in hospitalizations due to primary care sensitive conditions in this large Brazilian metropolis, while at the same time promoting greater health equity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
41

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 27 publications
4
33
0
41
Order By: Relevance
“…(10) Although the coverage of FHS has increased in Paraná (from 23% in 2000 to 60.2% in 2011), care quality is not uniform; in addition, the relation to causes considered sensible to primary care, such as bacterial pneumonias, is questioned if that level of care is less organized to respond to these diagnoses. (11) In relation to age range, the results corroborate a study of main causes of admissions by respiratory disease in children and adolescents in São Paulo. That study found that the frequency of hospital admission for pneumonia was higher in children younger than five years.…”
Section: Discussionsupporting
confidence: 79%
“…(10) Although the coverage of FHS has increased in Paraná (from 23% in 2000 to 60.2% in 2011), care quality is not uniform; in addition, the relation to causes considered sensible to primary care, such as bacterial pneumonias, is questioned if that level of care is less organized to respond to these diagnoses. (11) In relation to age range, the results corroborate a study of main causes of admissions by respiratory disease in children and adolescents in São Paulo. That study found that the frequency of hospital admission for pneumonia was higher in children younger than five years.…”
Section: Discussionsupporting
confidence: 79%
“…No âmbito nacional, há relatos da diminuição das taxas de ICSAP associadas ao crescimento de cobertura da ESF 11,17 . Ao contrário disso, no presente estudo, a cobertura da atenção primária à saúde, representada pela cobertura da ESF e do PACS, apresentou, na análise bivariada, uma discreta associação positiva com as internações sensíveis, ou seja, quanto maior a cobertura maior o número dessas hospitalizações.…”
Section: Discussionunclassified
“…Quanto a isso, Macinko 19 menciona que um dos entraves da sua utilização é o fato de que pode levar anos para que sejam estabelecidas tendências, assim como detecção de problemas em áreas pequenas e em mudanças pontuais. Outros estudos que demonstraram uma associação negativa da oferta de serviços de atenção básica e das internações sensíveis o fizeram por meio de análise de série temporal, enquanto, nesta pesquisa, considerou-se apenas o ano de 2010 2,11 .…”
Section: Discussionunclassified
“…Since this took place, studies have been undertaken in order to evaluate, even if indirectly, the quality of the healthcare offered in primary care, using data on potentially-avoidable admissions with the PHC services, demonstrating that the best coverage at this level of care is associated with the reduction of APCSC. [4][5] In Brazil, APCSC were responsible for 34% of admissions paid for by the Unified Health System (SUS), costing the system R$ 1.03 billion in costs resulting from hospital admissions; 51.9% of these admissions were of women. 6 Some studies have evidenced proportions of admissions due to PCSC in women which are 28% higher than those for men.…”
Section: Introductionmentioning
confidence: 99%